Systematic video recording of seated athletes during the shot-put event at the Sydney 2000 Paralympic Games - Frossard, L.; Stolp, S.; Andrews, M. (International Journal of Performance Analysis in Sport, 2004)
The purpose of this paper is to share useful and practical information coming out of the first experience of systematic video recording of seated shot-putters during the Sydney 2000 Paralympic Games. It is anticipated that this paper will provide valuable information to sport scientists facing the challenge of conducting performance analysis of able-bodied or disabled athletes, such as seated shot-putters, during world-class competitive events. More specifically, this paper provides (1) the practical aspects of the cameras` setup used during this systematic video recording, (2) the number and usability of attempts recorded, taking into consideration the impact of uncontrollable perturbing factors, and (3) recommendations to improve the video recording procedure in such conditions. Two operators recorded each put using two compact, high-speed digital video cameras placed in different locations such as right, left or front of the shot-putter. In this study, 15% of the attempts were not recorded, 72% were recorded and fully available for analysis, 10% were incomplete and 2% were obstructed (as a percentage of expected attempts). This study suggests that the increase of the number and usability of the attempts recorded relies on the number and position of cameras and the operators as well as on other facilitating actions.